2011
DOI: 10.1080/09540121.2010.543881
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the WHOQOL-HIV BREF among HIV-infected patients in Taiwan

Abstract: According to the World Health Organization (WHO), the quality of life (QOL) of an individual is essentially defined as the subjective evaluation by such individuals of their own personal life embedded within the context of their culture and values. In the present study, we set out to examine the reliability and validity of the WHOQOL-HIV BREF, a newly-developed, multi-dimensional instrument comprising 31 items designed to assess the QOL of people in Taiwan infected with human immunodeficiency virus (HIV). We c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
51
1
7

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(74 citation statements)
references
References 12 publications
15
51
1
7
Order By: Relevance
“…Similar effects in these items have been previously reported [13]. In line with prior validation studies [14,15], no floor and ceiling effects were observed on QoL domains.…”
Section: ) All Whoqol-hiv-bref Domains and Overallsupporting
confidence: 78%
See 3 more Smart Citations
“…Similar effects in these items have been previously reported [13]. In line with prior validation studies [14,15], no floor and ceiling effects were observed on QoL domains.…”
Section: ) All Whoqol-hiv-bref Domains and Overallsupporting
confidence: 78%
“…Evidence for convergent validity is supported by significant correlations with the general facet of QoL and the self-reported perception of general health. This pattern of associations was also demonstrated in other validation studies [13,15], and the strength of the associations was comparable to the reported in those studies. Potential limitations imposed by the sample, the sampling strategy and the study design should be acknowledged.…”
Section: ) All Whoqol-hiv-bref Domains and Overallsupporting
confidence: 76%
See 2 more Smart Citations
“…Both questionnaires were validated in various cultural settings and proved to have acceptable psychometric properties (e.g., Hsiung et al, 2011;Pereira, Martins, Alves, & Canavarro, 2014;Reychler, Caty, Vincent, Billo, & Yombi, 2013;Zimpel & Fleck, 2007). According to Skevington and O'Connell (2003), the WHOQOL-HIV-Bref, compared to other HIV-specific instruments, is culturally more sensitive particularly regarding the methodology underlying its development, therefore enabling cross-cultural comparisons.…”
mentioning
confidence: 99%